2020
DOI: 10.1111/beer.12285
|View full text |Cite
|
Sign up to set email alerts
|

Overall justice and supervisor conscientiousness: Implications for ethical leadership and employee self‐esteem

Abstract: Research on organizational justice demonstrates its consistent effect on employee organization‐based self‐esteem. However, little research considers how organizational justice affects employee organization‐based self‐esteem and when the relationship is attenuated. In an effort to extend the research regarding this particular relationship, we draw on social cognitive theory to suggest that supervisors’ perceptions of overall organizational justice trickle down to impact employees’ organization‐based self‐esteem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 114 publications
(236 reference statements)
0
32
0
Order By: Relevance
“…First, a Harman’s single-factor test revealed that no factor explained the majority of variance (Williams et al, 1989) and seven eigenvalues had values greater than one. Researchers have commonly used this test (e.g., Huang et al, 2017; Letwin et al, 2016; Rice, Young, et al, 2020). Second, CFAs also revealed that our five-factor model had an acceptable fit (χ 2 = 891.49, d f = 454, p < .01; RMSEA = .10; SRMR = .09).…”
Section: Methodsmentioning
confidence: 99%
“…First, a Harman’s single-factor test revealed that no factor explained the majority of variance (Williams et al, 1989) and seven eigenvalues had values greater than one. Researchers have commonly used this test (e.g., Huang et al, 2017; Letwin et al, 2016; Rice, Young, et al, 2020). Second, CFAs also revealed that our five-factor model had an acceptable fit (χ 2 = 891.49, d f = 454, p < .01; RMSEA = .10; SRMR = .09).…”
Section: Methodsmentioning
confidence: 99%
“…Another way of showing disrespect refers to acts that directly or indirectly contribute to someone's stress, for example when the superior causes additional work for their subordinates by not doing their own part properly or by not informing them sufficiently so that they cannot prepare for difficult situations in a proper way. As ethical leaders treat employees fairly, care for their concerns and display appropriate conduct (Rice et al , 2020), they are expected to avoid behavior that causes burnout and engage in behavior that promotes well-being. Research strongly suggests that people are highly concerned about being treated fairly and that unfair behavior impairs well-being (Meier et al , 2009).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Third, we extended the role of ethical leadership in reducing the occurrence of unethical marketing and selling practices in response to perceived market competition via moral disengagement. Despite the growing importance of ethical leadership in business ethics literature (Mansur et al., 2020; Pircher Verdorfer & Peus, 2020; Rice et al., 2020), its role in sales literature as a boundary condition has not been widely examined (Badrinarayanan & Ramachandran, 2019; Schwepker, 2019; Wu, 2017). Hence, this study integrates ethical leadership with contextual and individual factors in a single model to advance our understanding of ethical leadership in the context of sales ethics.…”
Section: Introductionmentioning
confidence: 99%